Mn2+ effect on manganese oxides (MnOx) nanoparticles aggregation in solution: Chemical adsorption and cation bridging. (December 2020) - Cheng, Haijun; Yang, Tao; Jiang, Jin; Lu, Xiaohui; Wang, Panxin; Ma, Jun
Abstract: Manganese oxides (MnOx ) and Mn 2+ usually co-exist in the natural environment, as well as in water treatments for Mn 2+ removal. Therefore, it is necessary to investigate the influence of Mn 2+ on the stability of MnOx nanoparticles, as it is vital to their fate and reactivity. In this study, we used the time-resolved dynamic light scattering technique to study the influence of Mn 2+ on the initial aggregation kinetics of MnOx nanoparticles. The results show that Mn 2+ was highly efficient in destabilizing MnOx nanoparticles. The critical coagulation concentration ratio of Mn 2+ (0.3 mM) to Na + (30 mM) was 2 −6.64, which is beyond the ratio range indicated by the Schulze-Hardy rule. This is due to the coordination bond formed between Mn 2+ and the surface O of MnOx, which could efficiently decrease the negative surface charge of MnOx . As a result, in the co-presence of Mn 2+ and Na +, a small amount of Mn 2+ (5 μM) could efficiently neutralize the negative charge of MnOx, thereby decreasing the amount of Na +, which mainly destabilized nanoparticles through electric double-layer compression, required to initiate aggregation. Further, Mn 2+ behaved as a cation bridge linking both the negatively charged MnOx and humic acid, thereby increasing the stability of the MnOx nanoparticles as a result of the steric repulsion of the adsorbed humic acid. The results of this study enhance the understanding of the stability of the MnOx nanoparticles in the natural environment, as well as in water treatments. Graphical abstract: Image 1 Highlights: Chemically adsorbed Mn 2+ efficiently decreased the surface charge of MnOx . Mn 2+ and Na + had a co-effect on the destabilization of MnOx nanoparticles. Mn 2+ increased the adsorption of HA onto MnOx through cation bridging. The steric repulsion of adsorbed HA enhanced the stability of the MnOx nanoparticles. Abstract : Main finding: Mn 2+ and Na + have a co-effect on the aggregation of nanoparticles; Mn 2+ increases the adsorption of humic acid onto MnOx through cation bridging effect.